Transcranial direct current stimulation over left inferior frontal cortex improves speech fluency in adults who stutter - Chesters, Jennifer; Möttönen, Riikka; Watkins, Kate E. (Oxford University Press, 2018)
Stuttering is a neurodevelopmental condition affecting 5% of children, and persisting in 1% of adults. Promoting lasting fluency improvement in adults who stutter is a particular challenge. Novel interventions to improve outcomes are of value, therefore. Previous work in patients with acquired motor and language disorders reported enhanced benefits of behavioural therapies when paired with transcranial direct current stimulation. Here, we report the results of the first trial investigating whether transcranial direct current stimulation can improve speech fluency in adults who stutter. We predicted that applying anodal stimulation to the left inferior frontal cortex during speech production with temporary fluency inducers would result in longer-lasting fluency improvements. Thirty male adults who stutter completed a randomized, double-blind, controlled trial of anodal transcranial direct current stimulation over left inferior frontal cortex. Fifteen participants received 20 min of 1-mA stimulation on five consecutive days while speech fluency was temporarily induced using choral and metronome-timed speech. The other 15 participants received the same speech fluency intervention with sham stimulation. Speech fluency during reading and conversation was assessed at baseline, before and after the stimulation on each day of the 5-day intervention, and at 1 and 6 weeks after the end of the intervention. Anodal stimulation combined with speech fluency training significantly reduced the percentage of disfluent speech measured 1 week after the intervention compared with fluency intervention alone. At 6 weeks after the intervention, this improvement was maintained during reading but not during conversation. Outcome scores at both post-intervention time points on a clinical assessment tool (the Stuttering Severity Instrument, version 4) also showed significant improvement in the group receiving transcranial direct current stimulation compared with the sham group, in whom fluency was unchanged from baseline. We conclude that transcranial direct current stimulation combined with behavioural fluency intervention can improve fluency in adults who stutter. Transcranial direct current stimulation thereby offers a potentially useful adjunct to future speech therapy interventions for this population, for whom fluency therapy outcomes are currently limited.